PROFIL GURU HARAPAN MASA DEPAN - A. Marjuni; Alwan Suban (Faculty of Tarbiyah and Teacher Training, 2020)
AbstrakGuru adalah pendidik profesional dengan tugas untuk mendidik, mengajar, membimbing, mengarahkan, melatih, menilai, dan mengevaluasi peserta didik pada pendidikan anak usia dini jalur pendidikan formal, pendidikan dasar, dan pendidikan menengah. Guru mempunyai kedudukan sebagai tenaga profesional pada jenjang pendidikan dasar, pendidikan menengah, dan pendidikan anak usia dini pada jalur pendidikan formal yang diangkat sesuai dengan peraturan perundang-undangan yaitu: pertama, pengakuan kedudukan guru sebagai tenaga profesional dibuktikan dengan sertifikat pendidik. Kedua, Kedudukan guru sebagai tenaga profesional berfungsi untuk meningkatkan martabat dan peran guru sebagai agen pembelajaran berfungsi untuk meningkatkan mutu pendidikan nasional ketiga, Kedudukan guru dan dosen sebagai tenaga profesional bertujuan untuk melaksanakan sistem pendidikan nasional dan mewujudkan tujuan pendidikan nasional, yaitu berkembangnya potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, serta menjadi warga negara yang demokratis dan bertanggung jawab. AbstractA teacher is a professional educator with the task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education, and secondary education. The teacher has a position as a professional at the level of basic education, secondary education, and early childhood education in the formal education pathways that are appointed by laws and regulations, namely: first, the recognition of the position of teachers as professionals as evidenced by certificates of educators. Second, the position of the teacher as a professional staff function to improve the dignity and the role of the teacher as a learning agent functions to improve the quality of national education. Third, the position of the teacher and lecturer as professional staff aims to implement the national education system and realize the national education goals, namely the development of the potential of students so that be a human being who believes and is devoted to Allah Almighty, noble, healthy, knowledgeable, competent, creative, capable, and becomes a democratic and responsible citizen.